Effectiveness of Grassroots NGOs: An Empirical Exploration. - Panda, Biswambhar & Pattnaik, Binay Kumar (2005)
The paper is a study of ‘effectiveness among grassroots environmental NGOs’ by defining and operationalizing it from the vantage point of a new social movement perspective. Hence a set of hypotheses based on the proposed relations between ‘NGO effectiveness’ and its social correlates have been formulated and verified. In this exercise while the ‘NGOs’ effectiveness’ makes the dependent variable, the level of bottom-up approach practised by these NGOs, their prevalent reward system, motivation of their employees, prevalent work culture and the prevalent sense of purpose among their employees make independent variables. The paper defines and measures each of these variables and examines the relation of the dependent with each of the independent variable. The empirical data source for the study has been 40 grassroots NGOs that primarily deal with environmental and ecological issues and are located in the coastal districts of Orissa, the south- eastern state of India.